The Analysis of Turkey’s Publications in Forensic Medicine Indexed in Science Citation Index Between 2000-2004 - Balcı, Yasemin; Altun, Gürcan; Teyin, Muharrem (The Bulletin of Legal Medicine, 2009)
It is important for scientists to share the studies they conduct with other researchers as well as following developments in their area. The best way to share the results of scientific studies which require a long time and a lot of effort with other scientists is to publish them in internationally accepted and distinguished journals. In this study, we aim at assessing international publications compiled through contributions of forensic medicine expert and their assistants in Turkey between 2000 and 2004. This has been carried out according to the criteria of the encouragement program of TUBITAK-International Scientific Publications and by analyzing the contribution of these publications to those in the scope of the Science Citation Index-Journal Citation reports in Turkey. Thus, we used the “Pub Med and Web of Science” data base. Between 01.01.2000 and 31.12.2004, in the journals in the scope of Web of Science data base, a total of 86 publications were produced by forensic medicine experts and their assistants. The ratio of contributions to the Turkey originated publications rose to 0.23% from 0.11% in the last two years. It determinated that 70 of the publications (81.4%) were full articles and 15 of them (17.4%) were partial articles. According to the criteria of the TUBITAK International Scientific Publications Encouragement Program, 3 of the publications (3.5%) took place A Group, 54 of them (62.8%) in the B Group and 23 of them (26.7%) in the C Group journal lists. The publications with four or more contributors make up of 79.1% of the total publications. With 24 (27.9%) of the publications. Forensic Science International had the most publications, with publications shown in journals concerning forensic science (Forensic Science International, American Journal of Forensic Medicine and Pathology, Journal of Forensic Sciences, International Journal of Legal Medicine) making up 39.5% of the total publications. The study aimed to contribute to the development of international publications in the field of forensic medicine.Key words: Forensic medicine. Science Citation Index, Turkey
Keywords: forensic medicine. science citation index; Turkey